EU Macro-Regional Strategies – A Great Solution for a Better Future: Array - Marchis, Gabriela (Journal of Danubian Studies and Research, 2021)
‘Prosperity through Diversity’ is the new aim of EU macro-regional strategies for the current programming period 2021-2027. Raising the awareness of local/regional authorities as actors of development is also a duty of academia. Danubius University of Galati through DAIE conferences ensures yearly a substantive and continued policy dialogue on the topic of Danube region development. In this light, this research paper tries to increase the knowledge sharing and the engagement of relevant actors in defining the new path of development of this area towards a greener, smarter, carbon-free and more social region. Coordination in policy approach and cooperation through networks, platforms and alliances at different level of governance, will increase the capacity of Romanian public administration to respond to the new challenges of EU development on its three dimensions: economic, social and territorial. Strengthen the role strategic thinking is the main objective of this paper. Good economic governance, including fair and inclusive mobilization of internal revenues and transparent management of public finances and efficient and inclusive public spending will make this region a successful example, but strategic thinking is a necessity.